1992
DOI: 10.1109/22.121728
|View full text |Cite
|
Sign up to set email alerts
|

On the quasi-TEM and full-wave approaches applied to coplanar multistrip on lossy dielectric layered media

Abstract: The characteristic parameters of coplanar multistrip lines embedded in multilayered lossless/lossy substrates are commonly computed by using either quasi-TEM or fullwave models. Several methods are provided in the literature to deal with this type of structure. In this paper a comparative study of quasi-TEM and rigorous solutions is carried out in order to establish criteria for the validity of the quasi-TEM approach. Reliable quasi-TEM and full-wave numerical data have been properly generated by applying an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Time-domain analysis of a system provides the behaviour of the signal over time and covers a wide range of frequency with a single run of simulation [1][2][3]. It is also the most suitable choice when it comes to a nonlinear system analysis because it describes the nonlinear system as a nonlinear system of differential equations, which is transformed to a system of difference equations and solved simply using an appropriate numerical method [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Time-domain analysis of a system provides the behaviour of the signal over time and covers a wide range of frequency with a single run of simulation [1][2][3]. It is also the most suitable choice when it comes to a nonlinear system analysis because it describes the nonlinear system as a nonlinear system of differential equations, which is transformed to a system of difference equations and solved simply using an appropriate numerical method [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the lack of complete agreement, a certain consensus was reached that the characteristic impedance given by the power-current (PI) definition (involving a two-dimensional (2-D) analysis of an infinite line) is the most appropriate for strip-like lines, whereas the power-voltage (PV) definition is the most appropriate for slot-like lines [3], [4], [6]. Other investigations have explored de-embedding schemes with three-dimensional (3-D) structures having practical excitations [7]- [9], where it was found that the values of the characteristic impedance turn out to be very close to those provided by the PI definition.…”
Section: Introductionmentioning
confidence: 99%
“…Choosing the fields, after some algebra on the LHS of (5) (making use of orthogonality relations), the LHS can be expressed as (6) where subindex stands for "transverse" to the propagation axis. If (1) is now introduced in the RHS of (5), the RHS can be rewritten as (7) where is a contour at 0 that is tangent to the conductor surface and surrounds the strip conductor.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous electromagnetic approaches have been published which contains results of numerical full‐wave or quasi‐TEM analyses. We can mention, the method based upon the classical mode‐matching procedure (Sorrentino et al , 1984), the spectral‐domain analysis method (Mu et al , 1986; Shibata and Sano, 1990; Mesa et al , 1992), and the finite element method (Aubourg et al , 1983) have been investigated for this structure. An edge effect enforced boundary element method has been used in capacitance matrix evaluation of multiconductor transmission line structures in Pan et al (1992).…”
Section: Introductionmentioning
confidence: 99%